Recent Advances in Antiviral Therapy for Chronic Hepatitis C - Akihiro Tamori; Masaru Enomoto; Norifumi Kawada (Hindawi Limited, 2016)
Hepatitis C virus (HCV) infection is a major worldwide health problem. Chronic infection induces continuous inflammation in the liver, progression of hepatic fibrosis, eventual cirrhosis, and possible hepatocellular carcinoma. Eradication of the virus is one of the most important treatment aims. A number of promising new direct-acting antivirals (DAAs) have been developed over the past 10 years. Due to their increased efficacy, safety, and tolerability, interferon-free oral therapies with DAAs have been approved for patients with HCV, including those with cirrhosis. This review introduces the characteristics and results of recent clinical trials of several DAAs: NS3/4A protease inhibitors, NS5A inhibitors, and NS5B inhibitors. DAA treatment failure and prognosis after DAA therapy are also discussed.